Tingkat Kecemasan Pasien Kardiovaskuler pada Masa Pandemi COVID-19 - Juli Andri; Padila Padila; Nur Afni Wulandari Arifin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the level of anxiety of patients with cardiovascular disorders during the COVID-19 pandemic in the work area of the Telaga Dewa Health Center, Bengkulu City. The type of research used in this research is quantitative research with a cross-sectional approach. The results showed that the level of anxiety of respondents who were included in the standard/not anxious category was 4 respondents (5.4%), mild anxiety was 27 respondents (36.5%), moderate anxiety was 33 respondents (44.6%), and anxious weight as many as 10 respondents (13.5%). In conclusion, the anxiety level of patients with cardiovascular disorders during the COVID-19 pandemic in the Telaga Dewa Health Center work area, Bengkulu City, was in the moderate anxiety category. Keywords: COVID-19, Cardiovascular, Anxiety Level